2022
DOI: 10.1136/lupus-2022-000668
|View full text |Cite
|
Sign up to set email alerts
|

Role of autoantibodies and blood–brain barrier leakage in cognitive impairment in systemic lupus erythematosus

Abstract: ObjectiveCognitive impairment is common in patients with SLE but the cause is unknown. The current cross-sectional study examined the association between select SLE-related autoantibodies, other serological biomarkers and extensive blood–brain barrier (BBB) leakage in patients with SLE with and without cognitive impairment. In addition, we determined whether the relationship between SLE autoantibodies, other biomarkers and cognitive impairment differed depending on the presence or absence of concurrent extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…While anticardiolipin antibodies have been positively linked to cognitive deterioration in adults with SLE 41 and in normal elderly individuals, 42 others could not prove this association. Hanly et al, 7 who have used dynamic contrast-enhanced MRI scanning, found that cognitive impairment in SLE was associated with blood–brain barrier leakage independently of the circulating autoantibody profile (including antiphospholipid).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While anticardiolipin antibodies have been positively linked to cognitive deterioration in adults with SLE 41 and in normal elderly individuals, 42 others could not prove this association. Hanly et al, 7 who have used dynamic contrast-enhanced MRI scanning, found that cognitive impairment in SLE was associated with blood–brain barrier leakage independently of the circulating autoantibody profile (including antiphospholipid).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Patients with SLE who experience a stroke and seizure may have CD in up to 50% of the cases, but patients without neurological manifestations or an active disease may also complain of these symptoms. 3 CD is considered one of the most common manifestations of neuropsychiatric lupus 7 ; however, because the numbers change, it is difficult to assess its exact prevalence, according to studies. This is because the studied samples are varied, there is no biomarker available, and it is difficult to attribute CD to the lupus itself, as several medications and complications may be implicated in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown an essential factor for IL-1b overexpression and the deterioration of tau phosphorylation function and tangle formation ( 50 ). Moreover, a higher level of IL-1b can hamper the amyloid-beta (Aβ) clearance functions of microglia ( 51 ) and increase blood-brain barrier permeability, which is mainly responsible for the accumulation of Aβ in the brain ( 19 , 52 , 53 ). Pro-inflammatory cytokines, such as TNF, IL-1, IL-6, and IL-17 in SRDs may increase the risk of dementia through cell apoptosis and neuronal damage ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the current evidence of SRDs, little information can be gathered if SRDs are related to dementia. Thus, we examined the relationship between SRDs and dementia risk through an updated systematic review of evidence ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-NR2 antibodies cross-react with anti-double-stranded DNA antibodies [ 82 ]. Anti-NR2 antibodies can enter the CNS via intrathecal IgG synthesis or by breaching the BBB [ 83 ]. The severity of BBB damage plays a significant role in diffuse NPSLE syndromes, including the potential acute confusional state, because it allows large titers of anti-NR2 to enter the CNS [ 84 ].…”
Section: Autoantibodies Can Lead To Neuronal Damage In Npslementioning
confidence: 99%